2017
DOI: 10.3390/app7101070
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of an Oscillatory-Type Tidal Current Powered Generator Based on Robotic Fish Technology

Abstract: Abstract:The generation of clean renewable energy is becoming increasingly critical, as pollution and global warming threaten the environment in which we live. While there are many different kinds of natural energy that can be harnessed, marine tidal energy offers reliability and predictability. However, harnessing energy from tidal flows is inherently difficult, due to the harsh environment. Current mechanisms used to harness tidal flows center around propeller-based solutions but are particularly prone to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Equation 16is substituted into (12) to (14), ℎ ( , , ) = ( , , ) − 0 ( , ), then continuity Equation 17and motion Equation 18of triangle grids are obtained by Galerkin method.…”
Section: Turbine Simplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 16is substituted into (12) to (14), ℎ ( , , ) = ( , , ) − 0 ( , ), then continuity Equation 17and motion Equation 18of triangle grids are obtained by Galerkin method.…”
Section: Turbine Simplificationmentioning
confidence: 99%
“…Gillibrand et al [11] adopted a three-dimensional (3-D) hydrodynamic model to consider the potential effects of energy extraction by an array of tidal turbines on ambient near-bed velocity field and local bed shear stress. Yamamoto et al [12] exploited ANSYS to select the best shape of oscillator, in order to efficiently harness the tidal flow energy in a cost-efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…They consider two specific types of oscillators, firstly a wing-type oscillator, in which the optimal elastic modulus is being sort, and secondly, the optimal selection of shape from 6 basic shapes for a reciprocating oscillating head-type oscillator. Analysis of the flow field clearly showed that the discontinuous flow caused by a square-headed oscillator results in higher lift coefficients due to intense vortex shedding, and that stable operation can be achieved by selecting the optimum length to width ratio [19]. Koca et al develop a complete non-linear dynamic model comprising entirely kinematic and hydrodynamic effects of Carangiform locomotion based on the Lagrange approach by adapting the parameters and behaviors of a real carp.…”
Section: Fish Inspired Robotsmentioning
confidence: 99%